PENEGAKAN HUKUM PEMBERIAN HAK RESTITUSI TERHADAP KORBAN TINDAK PIDANA PERDAGANGAN ORANG DALAM PERSEKTIF KEARIFAN LOKAL DI ACEH - Irwandi Irwandi (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2023)
Trafficking is a new form of slavery in the modern age. In the context of trafficking crimes, at least in Indonesia there are laws that guarantee respect for humanity and prosecution of all forms of injustice that can be used to take action against crimes that injure humanity, namely Law Number 21 of 2007 concerning the Eradication of Trafficking Crimes People (Law Trafficking).Article 48 paragraph (1) of Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons (Law Trafficking), states